2016
DOI: 10.2166/washdev.2016.148
|View full text |Cite
|
Sign up to set email alerts
|

When behavior change fails: evidence for building WASH strategies on existing motivations

Abstract: Despite increased efforts, an estimated 30-40% of rural drinking water initiatives in developing countries fail to provide sustainable solutions. The Sustainable Development Goal for water (SDG 6) challenges us to solve this problem to ensure availability and sustainable management of water and sanitation for all. In this paper, we explore one possible barrier to success: a potential misalignment between local and outside motivations. We address this problem by analyzing how strategies used to successfully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Community ownership . Without full commitment to a bottom-up community-based, participatory approach, there is the risk that rural communities, not fully engaged, will not adopt and maintain changed practices (Hall et al, 2016; Marshall and Kaminsky, 2016). Bond et al (2015) found that many water management committees (WMC) were no longer active and that WMCs were more effective ‘ when the community determines their structures rather than them being imposed, when they have strong links to existing leadership structures and when they have the necessary skills ’.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Community ownership . Without full commitment to a bottom-up community-based, participatory approach, there is the risk that rural communities, not fully engaged, will not adopt and maintain changed practices (Hall et al, 2016; Marshall and Kaminsky, 2016). Bond et al (2015) found that many water management committees (WMC) were no longer active and that WMCs were more effective ‘ when the community determines their structures rather than them being imposed, when they have strong links to existing leadership structures and when they have the necessary skills ’.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, it is preferable for community members to be trained in facilitation skills. Without this capacity for facilitation, key rWASH messages are not imparted, communities are not ‘triggered’ and projects can risk failure (Kar and Bongartz, 2006; Marshall and Kaminsky, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors at the personal and social level-such as social norms, status, self-efficacy convictions, and the like-have been shown to be important predictors for the success of promotion campaigns targeting a range of health-relevant behaviors [14][15][16][17]. Successful promotion strategies have also been shown to surpass outside stakeholders' project goals and definitions of outputs by rather taking into account multiple perspectives, especially local populations' views, attitudes, motivators, and fears [18].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies point to the idea of "behavior change" as the main difficulty or, as some have posited, the main opportunity to ISF adoption and ultimately an improved quality of life Marshall 2016;Riboli-Sasco, 2015;Nawab, 2006, Bartram, 2010. This agrees with others (Evans, 2005;Jenkins and Scott, 2007;Peat et al, 2010) that latrine use has much more to do with other barriers like convenience, comfort, privacy and safety.…”
Section: 1: Barriers and Approaches To Improved Sanitation Adoptionmentioning
confidence: 65%